EPID-29. THE INFLUENCE OF SOCIOECONOMIC FACTORS AND CANCER CARE RECEIVED AT DIFFERENT FACILITIES ON OUTCOME IN PATIENTS WITH GLIOBLASTOMA. (11th November 2019) - Li, Terry; Patel, Palak; Chou, Janice; Patel, Amie; Crispo, Sylvia; Utate, Minerva; Kurz, Sylvia
Abstract: BACKGROUND: Younger age and higher performance status are strong positive predictors of longer survival in patients with high-grade gliomas. In many cancers, disparities in race, gender, socioeconomic background, and immigration status were shown to influence outcome. Only few studies have investigated the impact of healthcare disparities in patients with glioblastoma, with conflicting results. We hypothesized that patient-specific and healthcare system-related factors influence the utilization of healthcare and impact outcome in glioblastoma patients. METHODS: This is a retrospective observational study in glioblastoma patients receiving care at a NCI-designated Comprehensive Cancer Center (CCC) or a City Hospital (CH). Patient information including demographics, insurance status, molecular characteristics, treatment details, and survival was retrieved from the medical record. RESULTS: 59 patients were included (CCC n=47, PCH n=12). There were 22 females and 37 males. Median age was 63.0 years at CCC, 54.0 years at CH (p = 0.023). The two groups significantly differed by race (p=0.004), insurance status (p< 0.001), median income by zip code (p=0.015), extent of resection (p=0.001), receiving radiotherapy (p=0.014), and receiving chemotherapy (p< 0.001). Median overall survival (mOS) was longer at CCC (17.9 months) versus at CH (4.4 months) (p=0.021). Univariate Cox regression analyses found significantly better survival for insured vs. uninsured patients (HR 0.035, 95% CI 0.002–0.611, p=0.022) and for married/domestic partnership (M/DP) vs. non-M/DP patients (HR 0.352, 95% CI 0.141–0.879, p=0.025). Care facility, race, income, and treatment received did not emerge as significant predictors. Multivariate analysis controlling for facility and age at diagnosis showed improved survival for M/DP versus non-M/DP patients (HR 0.267, 95% CI 0.103–0.691, p=0.006). CONCLUSION(S): Insurance status and marital status emerged as significant contributors to survival. They may serve as surrogate markers for socioeconomic class and social support. Differences in Cancer Care received at different facilities may influence outcome as well.